2012
DOI: 10.1089/aid.2011.0018
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and Baseline Renal Function Among HIV-Infected Persons in the SUN Study

Abstract: In the combination antiretroviral therapy (cART) era, renal dysfunction remains common. The Study to Understand the Natural History of HIV/AIDS in the Era of Effective Therapy (SUN) (ClinicalTrials.gov number, NCT00146419) is a prospective observational cohort study of HIV-infected adults. At baseline, comprehensive data were collected, including cystatin C and measures of renal function. Univariate and multivariate regression analyses were performed to identify factors associated with baseline renal dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…Similarly, uncontrolled HIV viremia has been linked to renal dysfunction in a large randomized trial [22]. Our findings of the association between uncontrolled HIV viremia with urinary biomarker elevation supports the findings from a recent cohort study which noted an association between detectable HIV RNA (> 400 copies/ml) and elevated cystatin C, another biomarker of renal function [23]. This suggests that the development of these biomarkers as clinical guides will need to take into account the medical history of the patient as well as the effectiveness of their HIV directed care.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, uncontrolled HIV viremia has been linked to renal dysfunction in a large randomized trial [22]. Our findings of the association between uncontrolled HIV viremia with urinary biomarker elevation supports the findings from a recent cohort study which noted an association between detectable HIV RNA (> 400 copies/ml) and elevated cystatin C, another biomarker of renal function [23]. This suggests that the development of these biomarkers as clinical guides will need to take into account the medical history of the patient as well as the effectiveness of their HIV directed care.…”
Section: Discussionsupporting
confidence: 88%
“…13 Also in this study a significant direct correlation between MDRD and CKD-EPI was found using Spearman correlation (r s = 0.94, p < 0.001). In another paper, 14 Dabrowska et al used paired t-test to demonstrate that GFR estimated by CKD-EPI was consistently lower than MDRD.…”
supporting
confidence: 62%
“…Twenty-six publications reported HBV infection prevalence [63, 65, 69, 71, 79-81, 89, 102, 106, 110, 123, 141, 144, 147, 150, 151, 154, 157, 159, 162, 165, 170, 172, 174, 175]. HBV infection was defined in 72% of individual studies as positive by HBV surface antigen test (see Supplemental Table S7 for all definitions).…”
Section: Resultsmentioning
confidence: 99%